ASSOCIATION BETWEEN ANXIETY SYMPTOMS AND DEGREE OF HYPERTENSION IN RURAL INDONESIA - Muhammad Al Anas,; Nanda Sari Nuralita, (International Journal of Innovations in Engineering Research and Technology, 2021)
Background: Hypertension is responsible for at least 45% of deaths caused by heart disease and 51% of deaths due to stroke. Hypertension is a condition that is often found in primary health care. There are complex psychological processes involved in connecting between psychological factors and hypertension that are still not fully understood. Because symptoms of anxiety or hypertension pose a significant challenge as a public health problem, the relationship between the two also attracts the attention of researchers.Objective: This study aims to determine the association between anxiety symptoms and degree of hypertension in Rural Indonesia. Method: This study used descriptive analytical method with cross sectional design. Data is processed using the SPSS Chi-Square test. Results: Most of the respondents are male, consist of 37 people (61.7%) and the age category of 36-45 years is the highest by 28 people (46.7%). As for the demographic characteristics of marital status, 51 people (85%) of all respondents were married. Most of respondents’ blood pressure category was found in the hypertension stage 1 group of 23 people (38.3%), and the moderate anxiety category was as many as 23 people (38.3%). The association between anxiety symptoms and degree of hypertension in rural Indonesia showed a p value of 0.0001 (p